Rapid Detection of HDC Gene in Enterobacter aerogenes from Fish Products Using In Silico PCR for Food Safety and Allergy Risk Assessment: Deteksi Cepat Gen HDC pada Enterobacter aerogenes dari Produk Perikanan Menggunakan In Silico PCR untuk Penilaian Keamanan Pangan dan Risiko Alergi - Firman Fajar Perdhana; Muhammad ‘Aidil Febriandito; Setyaning Pawestri; Made Gendis Putri Pertiwi; Mutia Devi Ariyana; Lalu Unsunnidhal; Ines Marisya Dwi Anggraini; Lulu Diani Zuhdia (Universitas Muhammadiyah Palu, 2025)
Histamine poisoning is a significant food safety concern associated with fish and fishery products. Enterobacter aerogenes is one of the histamine-producing bacteria capable of converting L-histidine into histamine through the histidine decarboxylase (HDC) enzyme. The accumulation of histamine in fish and fishery products can lead to allergic reactions and foodborne illnesses, highlighting the need for rapid detection methods. This study aimed to design and optimize primers targeting the HDC gene in E. aerogenes and validate their specificity using in silico PCR. The HDC gene sequence was retrieved from the NCBI GenBank database, and primers were designed using Primer3Plus software. The in silico PCR analysis was performed to assess the specificity of the primers against the genome of E. aerogenes and other histamine-producing bacteria species. The optimized Primer Pair 1 successfully amplified a 230 bp target region, showing high specificity for E. aerogenes in product size and annealing position with no cross-reactivity to other histamine-producing bacteria species. These findings demonstrate the potential of in silico PCR as a rapid and cost-effective screening tool for detecting histamine-producing bacteria in fish and fishery products. However, further in vitro validation is required to confirm the applicability of these primers in real-world food safety and allergy risk assessments.